(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
The social impact of ill health is on the rise, with some diseases affecting not only the health of individuals but also that of a nations economy with their increasing healthcare costs. The enormous complexity of human body offers scope to conceptualize its dynamic organization in a number of ways such as structural, biochemical, functional, etc. The conventional western medicine views the body from a structural perspective, whereas Ayurveda, the ancient medical system of India, understands the human body from the perspective of functions/Tridoshas (Vata, Pitta and Kapha). Ayurveda is a holistic science and Ayurvedic treatment aims not only at removal of disease, but also at the restoration of the equilibrium of bodily functions. These different viewpoints of Ayurveda and western medicine have resulted not only in the use of different terminologies and metaphors to explain the human system but also in their different approaches to health and illness. In the recent past there has been a growing interest in Ayurvedic system of Medicine and their relevance to public health. In this context, there is a critical need to mainstream Ayurveda into public health care to achieve the objective of improved access to healthcare facilities.